NEEM FRUIT MUCILAGE-AIDED MUCOADHESIVE MICROSPHERES OF ACYCLOVIR USING 32 FACTORIAL DESIGN WITH DESIGN EXPERT SOFTWARE (Applied Biological Research, 2023)
The study aims to investigate the mucoadhesive properties of neem fruit  mucilagebyincorporatingitintomucoadhesive microspheres with Acyclovir  (ACR) as a model drug. Nine interpretations of mucoadhesive microspheres  were made with carbomer-934P and varying proportions of neem fruit  mucilage (NFM). A central composite design with Design Expert software  to check the impact of independent variables (neem mucilage and carbomer  934P levels) on entrapment efficacy and mucoadhesion time. As part of  congeniality studies, the microspheres were examined for ACR content and  liberation. The study revealed that ACR entrapment increased with  increase in NFM levels in the formulations and that the mucoadhesion time  was greater in formulations with higher NFM levels. In the formulations  containing higher levels of NFM, the drug release was slightly reduced.  Acyclovir is capable of good stomach-specific drug delivery by carbomer  934P and its delivery is enhanced by neem fruit mucilage when prepared as  mucoadhesive microspheres.
Keywords: Acyclovir; anti-viral; design; microspheres; mucoadhesive; neem